2013
DOI: 10.1186/1471-2407-13-273
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib alleviates tamoxifen-instigated angiogenic effects by ROS-dependent VEGF/VEGFR2 autocrine signaling

Abstract: BackgroundTamoxifen (TAM) is widely used in the chemotherapy of breast cancer and as a preventive agent against recurrence after surgery. However, extended TAM administration for breast cancer induces increased VEGF levels in patients, promoting new blood vessel formation and thereby limiting its efficacy. Celecoxib (CXB), a selective COX-2 inhibitor, suppresses VEGF gene expression by targeting the VEGF promoter responsible for its inhibitory effect. For this study, we had selected CXB as non-steroidal anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 51 publications
2
55
0
Order By: Relevance
“…Tamoxifen is a competitive antagonist of estrogen, but seems to have antiangiogenic effects independent of, and in addition to, estrogen receptor content or its anti-estrogen effects (Kousidoua et al, 2008). It have been reported that tamoxifen treatment of breast cancer, induces an antiangiogenic response by an efficient decrease of VEGF both in vitro and in vivo (Garvin and Dabrosin, 2003;Garvin et al, 2005;Nilsson and Dabrosin, 2006;Kumar et al, 2013;Rajput et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is a competitive antagonist of estrogen, but seems to have antiangiogenic effects independent of, and in addition to, estrogen receptor content or its anti-estrogen effects (Kousidoua et al, 2008). It have been reported that tamoxifen treatment of breast cancer, induces an antiangiogenic response by an efficient decrease of VEGF both in vitro and in vivo (Garvin and Dabrosin, 2003;Garvin et al, 2005;Nilsson and Dabrosin, 2006;Kumar et al, 2013;Rajput et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…IHC for specific proteins were carried out on tumor tissue sections using Biogenex IHC detection system according to manufacturer's guidelines. 24,25 Prostaglandin E2 and VEGF quantification by ELISA Snap frozen tissue samples preserved in ¡80…”
Section: Western Blot and Immunohistochemistrymentioning
confidence: 99%
“…From the stored sample, level of VEGF in serum of treated and untreated groups were quantified using VEGF quantikine ELISA kit, R&D systems according to kit guidelines. 25 Toxicological study Gross behavioral examination All animals were inspected twice a day during the course of the study and monitored carefully during weighing/feeding period. Animals were observed for reaction to treatment such as changes in skin, fur, eyes, and mucous membranes.…”
Section: Western Blot and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, postulated mechanisms proposed for the antitumor activity of nonsteroidal anti-inflammatory drugs (NSAIDs) include reduction in prostaglandin E2, resulting in activation of apoptosis in tumor cells [49], restricted angiogenesis via down-regulation of VEGF expression [50], and reduced inhibition of NK cell activity [5,51].…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%